Rubella Antibody Levels in School-Aged Children in Newfoundland: Implications for a Two-Dose Rubella Vaccination Strategy - Samuel Ratnam; Roy West; Veeresh Gadag; Brett Williams; Elizabeth Oates (Canadian Journal of Infectious Diseases)
OBJECTIVE: To determine the prevailing levels of rubella immunity among school-aged children who received a single dose of measles-mumps-rubella (MMR) vaccine at one year of age.